Pembuatan Aplikasi Customer Relationship Management Berbasis Website untuk Membantu Penjualan dan Analisis Penjualan Produsen Sepeda - Agustinus Ivan Suryadi; Yulia Yulia; Anita Nathania Purbowo (Jurnal Infra, 2017)
Companies that have been in the bicycle industry for over 20 years is located in Sidoarjo, and has more than 100 kinds of goods production to fullfill domestic and international market. Unfortunately, so far in this bike manufacturer company reports on customers recorded manually by making a written report on what it get. Because of that, the performance of the sales agent is hampered to keep information about customers well. It was not in accordance with the definition of Customer Relationship Management (CRM) ,CRM which is defined as the process of creating and maintaining relationships with customers. CRM itself is an information system that allows organizations to connect with customers, collecting, storing and analyzing customer data to provide a comprehensive view of their customers.This CRM aplication has features to help bike company manufacturers to monitor the performance of their sales agents directly, facilitate the sales agent in conducting the business process in question, and get help to analyze the sales of goods purchased by the customer. Making of this aplication is using laravel framework as well as utilizing Google Maps and Google Calendar API to complement the functionality of this aplication.The results obtained from the distribution of questionnaires to sales agents on applications that have been made is this aplication can run with either views. The application also provides ease of use and in accordance with the needs of sales agents. Maintaining a good relationship between the company and the customers are the focus of this program.